2013
DOI: 10.1155/2013/817693
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEffect of Arsenic Trioxide on Keap1-p62-Nrf2 Signaling Pathway in Mouse Liver: Expression of Antioxidant Responsive Element-Driven Genes Related to Glutathione Metabolism

Abstract: Arsenic is a Group I human carcinogen, and chronic arsenic exposure through drinking water is a major threat to human population. Liver is one of the major organs for the detoxification of arsenic. The present study was carried out in mice in vivo after arsenic treatment through drinking water at different doses and time of exposure. Arsenic toxicity is found to be mediated by reactive oxygen species. Nuclear factor (erythroid-2 related) factor 2 (Nrf2)/Keap1 (Kelch-like ECH-associated protein 1)/ARE (antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Recently, epidemiological studies have shown that chronic arsenic exposure is associated with the development of various vascular diseases . Liver and kidney are two important organs in the phase I and II detoxification processes in arsenic toxicity . The primary target cells of arsenic toxicity is in blood vessel walls .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, epidemiological studies have shown that chronic arsenic exposure is associated with the development of various vascular diseases . Liver and kidney are two important organs in the phase I and II detoxification processes in arsenic toxicity . The primary target cells of arsenic toxicity is in blood vessel walls .…”
Section: Introductionmentioning
confidence: 99%
“…), whereas decreased GSH levels in human multiple myeloma cells increase the sensitivity of tumor cells to arsenic trioxide (Srivastava et al . ). Therefore, the GSH content of glioma cells is closely related to the overall regulation of redox status and drug response of cells (Backos et al .…”
mentioning
confidence: 97%
“…In order to cope with this stress, the activity of the CAT enzyme which is responsible for the formation of oxygen and water by breaking down hydrogen peroxide (H 2 O 2 ) was also found to et al, 2019). Pb-induced stress may disrupt cysteine residues of Keap1, which results in release of Nrf2 from Keap1 and Nrf2 translocates into nucleus subsequently for the induction of antioxidant response pathway (Srivastava et al, 2013). Reports on Nqo1 protein expression in fish after Pb exposure is scarce.…”
Section: Discussionmentioning
confidence: 99%